Inclusive Education : Accommodations, Expectations, and Support - Moaven, Behnaz (My University, 2023)
Inclusion has been a subject of extensive research in education, gaining increasing importance in classroom practices. This study aimed to investigate the beliefs of primary school teachers in Finland regarding the delicate balance between providing accommodations and maintaining high expectations for all students in inclusive classrooms. Semi-structured interviews were conducted with eight primary school teachers to explore their perspectives on navigating accommodations and expectations. The interviews also delved into the challenges faced by teachers in this regard and the support they deemed necessary. The findings highlighted that the teachers advocated for offering all possible accommodations that benefit learning while simultaneously holding high expectations for students, irrespective of their abilities. Notably, the study revealed that the shortage of teacher assistants posed a significant challenge for teachers. Additionally, teachers expressed that they faced constant challenges in dealing with severe behavioural issues, emphasizing the need for increased assistance in such cases. They also stressed the importance of accurate diagnosis and enhanced collaboration among teachers, parents, and school counsellors. Furthermore, the results confirmed prior research that inclusion fosters acceptance among mainstream students and creates a sense of community and belonging for students with special needs. However, the study identified the necessity for further research to improve the implementation of Finland's three-tiered support system, ensuring equal opportunities for all students.
Keywords: Inclusion, Inclusive practices, Accommodations, Expectations, Special Needs students, Mainstream students, Support